UPAYA MENINGKATKAN RASA PERCAYA DIRI DENGAN MENERAPKAN STRATEGI PEER TUTORING MTs MUHAMMADIYAH 22 PADANGSIDIMPUAN - Piki Fatwani Nasution; Benny Sofyan Samosir; Masdelima Azizah Sormin (Jurnal Karya Pendidikan Matematika, 2021)
The problem in this study is the students' low self-confidence. To increase students' self-confidence in mathematics lessons on set material with peer tutoring strategies. The results of students' mathematics tests using the Peer Tutoring strategy in class VII A MTs Muhammadiyah 22 Padangsidimpuan were proven by the results of the mathematics test of students in cycle I obtained an average of 51.42% and in cycle II 82.85% the average increase from cycle I to cycle II was 31.43%. Based on observations of teacher performance, there was an increase in the cycle where I obtained an average value of 58.50%, cycle II obtained an average value of 88.00%, an average increase of 29.50%. Based on observations, teacher activity also increased where the first cycle obtained an average of 64.55% and the second cycle was 81.55% and an increase in the average value of 17.00%. Based on the research results, it can be denied that using the Peer Tutoring strategy can increase student self-confidence and teacher performance in class VII A MTs Muhammadiyah 22 Padangsidimpuan.